An Analysis of Spatial Construction in Pictorial Art from the Perspective of Formalism - Feng, Hanping; Shahir, Safrizal (Harmonia: Journal of Arts Research and Education, 2024)
“Space,” as a fundamental conceptual term, has been frequently and widely applied within various disciplines, such as sociology, architecture, philosophy, math, art, and so forth. In pictorial art, the term “space” is often used as a lens to understand specific concepts or artworks. This study aims to explain and describe pictorial spatial construction in paintings by applying various approaches. However, in the field of formalist analysis over the past century, except for a few formalist critics who have engaged with pictorial space, few have attempted to use creative methodologies to systematically analyze how pictorial space is constructed in the painting, particularly in works by contemporary painters. Therefore, to fill in this lacuna in the research, this study utilizes new formal analytical methods to analyze and explain spatial construction in paintings. In terms of the method of analysis, this study analyzes a sample of Western contemporary paintings and utilizes the approaches of the overlap of the abstract and the figurative, parallel narratives existing in multiple spaces, and the juxtaposition of different material dimensions, respectively, to rethink the method of spatial construction in the painting. The result concludes that paintings are an essential research object within visual art. The construction of image space is rich and includes multiple layers of meaning. The overlapping of abstract space (sensibility) and figurative space (rationality), as well as the coexistence of this contradictory system, enables artists to discover more possibilities when creating works and effectively enrich visual effects and textures in their paintings.